Income Inequality – Empirical Study of 34 Provinces in Indonesia - Setiawan, Mulyo Budi; Nawatmi, Sri; Nusantara, Agung (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
This research aims to find out what variables determine income inequality in 34 provinces in Indonesia 2018 - 2021. The method used in this research is pooling data or panel data. There are 3 models available in panel data, namely the PLS (pooled Least Square) model, FEM (Fixed Effect Model) and REM (Random Effect Model). Before analyzing, the first step is to determine the best model from the 3 models. The Chow test results show that the best model between PLS and FEM is FEM. To determine which model should be chosen between FEM and REM, the Hausman test is used, and the better model is FEM. Therefore, in this study FEM was used to estimate income inequality in 34 provinces in Indonesia. The estimation results show that of the 3 independent variables used in the estimation, only the HDI variable (human development index) influences income inequality in 34 provinces in Indonesia with a negative sign. Other variables, GRDP per capita and open unemployment rate do not affect income inequality.